Measurements of oxygenation and perfusion in skeletal muscle using multiple microelectrodes. - Greenbaum, A; Etherington, P; Manek, S; O'Hare, D; Parker, K; Green, C; Pepper, JR; Winlove, C (1997)
This paper describes an apparatus to measure tissue oxygenation and perfusion (as measured by the wash-in rate of gaseous hydrogen) simultaneously at multiple points in muscle using needle microelectrodes. The development of suitable electrodes and apparatus is described, as well as the development of the method and its validation. In particular, the potential for tissue damage secondary to electrode insertion, the need for in vivo voltammetric determination of the operating potential and the extent of any electrode-tissue and of electrode-electrode interactions are explored, and are shown to be insufficient in magnitude to affect the technique. Its subsequent use to characterise oxygenation and perfusion in rabbit skeletal muscle at rest is also described. In resting tibialis anterior muscle of the rabbit the mean pO2 was 18 +/- 13.3 mm Hg and the mean perfusion was 4.4 +/- 1.3 ml s-1 100 g-1. There was a heterogeneity in simultaneously-measured values of pO2 and perfusion at different points within muscle, and also a temporal variation at the same site. The spans between the highest and lowest simultaneously-measured values of pO2 in muscle ranged from 14 to 80 mm Hg, and for perfusion, from 1 to 12 mls-1 100 g-1. No significant correlation was evident from histological examination between either pO2 or perfusion and surrounding fibre type or capillary density.